Metallic fluoride complexes as phosphate analogues for structural and mechanistic studies of phosphoryl group transfer enzymes - Goličnik, Marko (Acta chimica slovenica, 2010)
There have been intensive efforts to try to understand the details of phosphoryl transfer reactions extending from nonenzymatic (or enzyme model) systems to the mechanisms of the enzyme catalysed reactions. As phosphate analogues, few metallic fluorides AlFx, BeFx and MgFx affect the activity of avariety of phosphoryl transfer enzymes, and it is accepted that these small inorganic complexes are useful chemical probes for structural and mechanistic studies in enzymology because they are able to mimic phosphoryl group in ground state (BeFx) as well as in transition state (AlFx,Mg-Fx). Al3+ and Be2+tend to form stable complexes with different fluoride anions (x=1 to 4) spontaneously in aqueous solution but Mg2+ does not. BeFx geometry is strictlytetrahedral resembling the phosphate ground state when bound to an acyl group of protein active site (phosphorylated acyl groups are unstable otherwise), or the Michaelis complex when BeFx concominantly with nucleoside diphosphate replaces gamma-phosphate group in nucleoside triphosphate sites. AlFx and MgFx are identified as enzymatic analogues of phosphoryl transition state where both are able to form different coordination geometries within theenzyme active sites: trigonal bipyramidal (AlF3 and MgF3-) or octahedral (AlF4- or Mg-F42-). The geometry and charge of MgF3- are the best suited to mimicking the trigonal planar PO3- moiety of phosphoryl transfer transition state but MgF3- does not, unlike aluminum and beryllium fluoride complexes, exists in solution and can be assembled and stabilized in suitable active siteonly. Therefore it is particularly interesting to characterize as a potentially highly accurate transition state analogue and may be the best reagent of choice for studying phosphoryl transfer reactions in future.
Keywords: aluminij; aluminum; berilij; encimi; fluoridi; fosforilacija; fosfotransferaze; kataliza; magnezij; transferaze